IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV UPT SDN 3 TAROWANG KABUPATEN JENEPONTO - Siti Nurfarida; Subaedah; Martini; Muh. Aidil Sudarmono R; Ahmad Wakka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of the Problem Based Learning (PBL) learning model and the improvement of student learning outcomes in the subject of science for grade IV of UPT SDN 3 Tarowang, Jeneponto Regency. The type of research used is Classroom Action Research (CAR) which was carried out in two cycles, including the planning, implementation, observation, and reflection stages, with 27 students as research subjects. The results showed that the implementation of PBL was carried out through the stages of problem presentation, group discussion, investigation, and presentation of results. In addition, there was an increase in student learning outcomes, namely in the pre-cycle an average of 65 (18.51%), increasing in cycle I to 74.55 (74.07%), and in cycle II reaching 84.81 (88.88%). Thus, it can be concluded that the Problem Based Learning (PBL) model is effective in improving student learning outcomes in the subject of science for grade IV of UPT SDN 3 Tarowang, Jeneponto Regency.